JAYADEWATA DAN PRASASTI KEBANTENAN (1428-1521 MASEHI) - Richadiana Kartakusuma (Berkala Arkeologi, 1994)
This article will not reveal the theory of Karesian. Instead, this article will explain the meaning behind Jayadewata's actions for the inauguration of Kabuyutan and Kawikwan. It related to Jayadewata's position as an actor. That is because written sources always based on reasons, goals, and meanings. The reason (sambandha) can often be known directly and written in the inscription (explicit), while the purpose and meaning are more implicit. Therefore, efforts to find out Jayadewata's actions in the Kebantenan inscription will be compared to other written sources in the form of Sundanese inscriptions and literatures. Ethnographic analogy is also conducted as a supporting comparative method.